Kelayakan Usahatani Cabai Rawit Di Subak Kacang Dawa, Desa Gelgel, Kecamatan Klungkung, Kabupaten Klungkung - Noviana Damma; Putu Fajar Kartika Lestari; Luh Putu Kirana Pratiwi; Ida Ayu Made Dwi Susanti (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
The objectives of the study were: to analyze the feasibility of cayenne pepper farming in Subak Kacang Dawa, Gelgel Village, Klungkung District, Klungkung Regency, the research was conducted through a survey of 30 farmers determined through a Population Data,The results of this study indicate that cayenne pepper farmers get a more decent income. According to information from the Central Statistics Agency no. 54/08th.xvi, August 1, 2013, the production of cayenne pepper in Indonesia in 2011 was 594.22 thousand tons and in 2012 it was 702.25 thousand tons, an increase of 108.03 thousand tons (18.18 percent). This increase was caused by an increase in productivity of 0.74 tons per hectare (14.77 percent) and an increase in harvested area of ​​3.38 thousand hectares (2.85 percent). however, for the province of Bali, there has been a decline in the productivity of cayenne pepper. In 2011, the production of cayenne pepper in the province of Bali was 17.055 tons and in 2012 it was 16,041 tons, decreased by 1,014 tons. This is due to the reduced area of ​​​​farmers' land due to the conversion of land for chili cultivation and pest attacks and contracting diseases that have not been overcome by farmers